Helicobacter pylori and Campylobacter jejuni bacterial holocytochrome c synthase structure-function analysis reveals conservation of heme binding - Tania Yeasmin; Susan C. Carroll; David J. Hawtof; Molly C. Sutherland (Communications Biology, 2024)
Abstract Heme trafficking is essential for cellular function, yet mechanisms of transport and/or heme interaction are not well defined. The System I and System II bacterial cytochrome c biogenesis pathways are developing into model systems for heme trafficking due to their functions in heme transport, heme stereospecific positioning, and mediation of heme attachment to apocytochrome c. Here we focus on the System II pathway, CcsBA, that is proposed to be a bi-functional heme transporter and holocytochrome c synthase. An extensive structure-function analysis of recombinantly expressed Helicobacter pylori and Campylobacter jejuni CcsBAs revealed key residues required for heme interaction and holocytochrome c synthase activity. Homologous residues were previously identified to be required for heme interaction in Helicobacter hepaticus CcsBA. This study provides direct, biochemical evidence that mechanisms of heme interaction are conserved, leading to the proposal that the CcsBA WWD heme-handling domain represents a novel target for therapeutics.